Bilateral first metatarsal stress fractures in a field hockey player - Metz, J. P. (The Physician and Sportsmedicine, 2005)
First metatarsal stress fractures are uncommon in young athletes, and to have them occur bilaterally is even more unusual, as in this case of a 14-year-old female field hockey player. The patient sought treatment after several days of bilateral foot pain with swelling and tenderness to palpation over the proximal aspect of the first metatarsals. Initial plain x-rays were negative, but a subsequent bone scan and MRI revealed bilateral first metatarsal stress fractures. The patient was successfully treated with relative rest and rigid-soled shoes. Clinicians should be aware that initial x-rays may not reveal first metatarsal stress fractures, and further imaging may be needed.